Supporting best practice in reflexive thematic analysis reporting in Palliative Medicine : A review of published research and introduction to the Reflexive Thematic Analysis Reporting Guidelines (RTARG) - Braun, Virginia; Clarke, Victoria (Palliative medicine, 2024)
Reflexive thematic analysis is widely used in qualitative research published in , and in the broader field of health research. However, this approach is often not used Common problems in published reflexive thematic analysis include assuming thematic analysis is a singular approach, rather than a family of methods, confusing themes and topics, and treating and reporting reflexive thematic analysis as if it is atheoretical. We reviewed 20 papers published in between 2014 and 2022 that cited Braun and Clarke, identified using the search term 'thematic analysis' and the default 'relevance' setting on the journal webpage. The aim of the review was to identify common problems and instances of good practice. Problems centred around a lack of methodological coherence, and a lack of reflexive openness, clarity and detail in reporting. We considered contributors to these common problems, including the use of reporting checklists that are not coherent with the values of reflexive thematic analysis. To support qualitative researchers in producing coherent and reflexively open reports of reflexive thematic analysis we have developed the (the RTARG; in Supplemental Materials) informed by this review, other reviews we have done and our values and experience as qualitative researchers. The RTARG is also intended for use by peer reviewers to encourage methodologically coherent reviewing. Methodological incoherence and a lack of transparency are common problems in reflexive thematic analysis research published in . Coherence can be facilitated by researchers and reviewers striving to be - thoughtful, deliberative, reflexive and theoretically aware - practitioners and appraisers of reflexive thematic analysis and developing an understanding of the diversity within the thematic analysis family of methods.